Response of the Danube River Floodplain to Flood Events During 2002-2007 Period - Lehotský, Milan; Novotný, Ján; Szmańda, Jacek (Quaestiones Geographicae, 2010)
The relationship between floods and their geomorphic effect is discussed in this article. Almost every flood event is registered in overbank alluvia. We investigated sediment structures and textures as a response to three flood events occurred during 2002-2007 period on the Danube River floodplain in Bratislava. The change in sedimentation is the effect of floodwater flow energy changeability in the channel and floodplain. Generally, three main phases of energy flow changes of floods are recognised and thus the complete flood record can be expressed as the set of three layers. We also analysed conditions of the overbank sedimentation based on the shape and size of sedimented particles. Results show a relatively high variability of sedimentation processes during floods. The total amount of new overbank sediment accumulated in the 2002-2007 period, its texture characteristics and spatial distribution do not depend only on flood discharge, but also on the drainage basin sources of floodwater and sediment.